The effect of argumentation applications on fifth grade students' academic achievement and decision-making skills - Tümoğlu, Emine; Memiş, Esra Kabataş (American Journal of Education and Learning, 2025)
This study examined the effect of argumentation applications on academic achievement and decision-making skills. Employing a mixed-methods approach, the study was conducted with 35 fifth-grade students attending a boarding secondary school in the Eastern Anatolia Region during the second term of the 2021–2022 academic year. There were 17 students in the control group and 18 in the experimental group. The study was conducted over five weeks during the 'Electric Circuit Elements' unit. Data were collected using an achievement test, a decision-making skills scale, and semi-structured interviews. The achievement test and decision-making skills scale were administered as pre- and post-tests, while semi-structured interviews were conducted at the end of the study to gather students' opinions on the application. Independent samples t-test and ANCOVA analyses were used to analyze the quantitative data. Qualitative data were analyzed by listening to interview recordings, converting them into written documents, and coding them to identify themes. The achievement test revealed a significant difference in favor of the experimental group compared to the control group. The ANCOVA results, which controlled for pre-test scores on the decision-making scale, indicated a significant improvement in decision-making skills for the experimental group. Qualitative analysis showed that the application positively influenced students' attitudes towards learning and the course.